Brazilian Nursing Process Research Network contributions for assistance in the COVID-19 pandemic - Alba Lúcia Bottura Leite de Barros; Viviane Martins da Silva; Rosimere Ferreira Santana; Agueda Maria Ruiz Zimmer Cavalcante; Allyne Fortes Vitor; Amália de Fatima Lucena; Anamaria Alves Napoleão; Camila Takao Lopes; Cândida Caniçali Primo; Elenice Valentim Carmona; Erika Christiane Marocco Duran; Howard Karl Butcher; et al. (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to describe the theoretical construction process of nursing process support documents in COVID-19 care scenarios. Methods: an experience report of the joint activity of the Brazilian Nursing Process Research Network (Rede de Pesquisa em Processo de Enfermagem) composed of Higher Education and Health Institution researchers in Brazil. Results: five instruments were organized collectively, involving the elements of nursing practice (nursing diagnoses, outcomes and interventions) in assistance for community; for patients (with suspected or mild, moderate, and critical COVID-19 and residents in Nursing Homes); for nursing workers' health support, also subsidizing registration and documentation during the COVID-19 pandemic. Final considerations: valuing the phenomena manifested by families/communities, patients and health professionals is essential for early detection, intervention, and prevention of diseases.